Self Confidence Konten Kreator Tiktok Makassar : Efek Hate Comment Dan Mental Health Melalui Apresiasi - Guntur, Ihsan; Akil, Nasriah; Misbahuddin; Taufik, Imran; Abdullah (Jurnal Online Manajemen ELPEI, 2024)
This research aims to find out how much trust each content creator has in Makassar, seen from the number of bad comments, their mental readiness and from the amount of appreciation,This research aims to find out whether there is an influence of Hate Comments and Mental Health on Self Confidence through Appreciation of Content Creators of the TikTok Application in Makassar. This research method uses a questionnaire in taking research samples. This research technique uses a smart PLS application with 73 respondents. The research results have been tested for validity and reliability, as well as Specific Direct Effects and Specific Indirect Effects and Hypothesis Testing.The research results show that a person's self-confidence is most influenced by themselves, not external influences. If someone is able to manage their mental health well, and for the Hate comment phenomenon, it will have an effect if there is appreciation from other people. So to support someone having Self Confidence, good mental health is needed which will of course support him to become a quality human resource and conversely if someone is unable to manage his mental health then his self confidence will decrease.